Financial Policy and Employee Behavior in Higher Education; The Planned Behaviour Approach with MARS Model - Syarifudin, Syarifudin (JURNAL AL-TANZIM, 2023)
This paper aims to analyze the impact of financial policies on employee behaviour at a university in East Kalimantan, which is analyzed using the theory of planned behaviour with MARS model. This study used a qualitative case study type approach, in which researchers used interviews, observation and documentation to obtain accurate information and data. Data analysis was carried out through data collection, data reduction, data display, and drawing conclusions. The results of the study show that transparent and accountable financial policies have a pretty good impact on the behaviour of the academic community at the Muhammadiyah University of Berau, starting from building good employee motivation, optimizing the implementation of the tri dharma of higher education, creating a sense of individual ownership of the organization and creating an excellent organizational culture. This research contributes to the importance of leaders in conducting their financial analysis appropriately and based on local wisdom so that the resulting policies will tremendously impact organizational progress.